A long-term study of stable isotope ratios of fingernail keratin and amino acids in a mother-infant dyad - Harris, Alison J T; Santos, Guaciara M; Malone, Kaelyn O; Van Der Meer, Marcel T J; Riekenberg, Philip; Fernandes, Ricardo (American journal of biological anthropology, 2024)
OBJECTIVE: To evaluate the potential of compound-specific isotope analysis of amino acids (CSIA-AA) for investigating infant feeding practices, we conducted a long-term study that compared infant and maternal amino acid (AA) nitrogen isotope ratios. MATERIALS AND METHODS: Fingernail samples were collected from a single mother-infant dyad over 19 months postpartum. Carbon and nitrogen stable isotope ratios were measured in the bulk keratin of the fingernail samples. Selected samples were then hydrolyzed and derivatized for compound-specific nitrogen isotope analysis of keratin AAs. RESULTS: As in previous studies, infant bulk keratin nitrogen isotope values increased during exclusive breastfeeding and fell with the introduction of complementary foods and eventual cessation of breastfeeding. Infant trophic AAs had elevated nitrogen isotope values relative to the mother, while the source AAs were similar between the mother and infant. Proline and threonine appeared to track the presence of human milk in the infant's diet as the isotopic composition of these AAs remained offset from maternal isotope values until the cessation of breastfeeding. DISCUSSION: Although CSIA-AA is costly and labor intensive, it appears to hold potential for estimating the duration of breastfeeding, even after the introduction of complementary foods. Through the analysis of a full suite of AAs, it may also yield insights into infant physiology and AA synthesis.
Keywords: novorozenec; kojení; Carbon Isotopes; Infant, Newborn; amino acids; keratiny; Infant; Humans; kojenec; Nitrogen Isotopes; mateřské mléko; Female; dospělí; Nails; lidé; aminokyseliny; Amino Acids; Adult; ženské pohlaví; Milk, Human; izotopy dusíku; izotopy uhlíku; breastfeeding; weaning; Breast Feeding; nehty; fingernails; Keratins; nitrogen